UJI EFEK GEL EKSTRAK ETANOL DAUN TEMBELEKAN (LANTANA CAMARA LINN.) TERHADAP PENYEMBUHAN LUKA SAYAT PADA KELINCI (ORYCTOLAGUS CUNICULUS) - Surya Ningsi; Khairunnisa Khairunnisa; Nur Ida (Universitas Islam Negeri Alauddin Makassar, 2015)
Research Test The Effect Gel Ethanolic Extract of Tembelekan Leaf (Lantana camara L.) to cuts wound healing in Rabbits (Oryctolagus cuniculus) as been done with the objective to determine the effectiveness of Tembelekan (Lantana camara L.) leaf ethanol extract gel to healing cuts wound in rabbits. The method used were extraction of the sample is by maceration, Formulation gel with varian consentration ethanolic extract of Tembelekan leaf (Lantana camara L.) were 1%, 2%, 4% and base gel without extract, test the effect in skin rabbits has been cuts wound healing in skin rabbitsfor all of the formula, positive control and negative control. Result of Research were given for extract 1%, 2%, dan 4%, positive control, and negative control average on the 12th, 11th, 9th, 6th, and 14th. From the result of statistical test completely randomized design (CRD) and the least significant difference test (LSD) can be conclueded that gel were given more effectif are ethanolic of Tembelekan (Lantana camara L.) extract content of 4%.